Outcome of Hemispherectomy for Refractory Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The clinical features, presurgical workup, and postoperative outcome of 39 patients with medically intractable epilepsy who underwent hemispherectomy from 1996 to 2005 are reported from University of Sao Paulo, Brazil.